Characterization of Junction and Junction-Less NMOS at Various Parametric Changes - Tawseef Ahmad Wani, Birinderjit Singh Kalyan (International Journal of Advanced Science and Technology, 2020)
In this paper, a Double Gate Negative Channel Metal Oxide Semiconductor (DG-NMOS) is simulated and characterized under Junction and Junction-Less Technology using the software Cogenda Visual TCAD. The output and transfer characteristics for junction-less technology are found to be better and thus, taken into consideration for further study at different parameter variations to obtain an optimal Junction Less Double Gate NMOS (JL DG-NMOS). The parameters varied are the substrate materials, channel thickness and doping levels of the channel. From analyzing the characteristics obtained, it is found that variation in the parameters changes the operating regions of a device. To obtain optimal performance it is found that the choice of parameters to be used depends on applications and operating regions of the device illustrated in this paper.